Effects of adopting IFRS 9 for the audit of financial instruments in non-financial companies - Shirley Franco da Silva; José Alves Dantas (Revista Ambiente Contábil)
Objective: The aim of this study is to determine the effects of adopting IFRS 9 for the auditing of financial instruments in non-financial companies in Brazil.